Decision Support System for Supplier Selection using Analytical Hierarchy Process (AHP) Method - Juliana, Juliana; Jasmir, Jasmir; Jusia, Pareza Alam (Universitas Negeri Semarang, 2017)
Technological growth is characterized by a variety of technological finds and computational methods used to facilitate human work in the era of globalization that is the method of Decision Support System (DSS) that helps decision makers to use data and models to solve problems that are not Structured. Toko Harapan Baru in making decisions in determining the best suppliers still use intuition, analysis, calculation and comparison of the manual in determining the supplier of goods to his shop takes a long time, the difficulty of searching data because there is no data processing cause is quite complicated without any particular method which gives inaccurate results. Then, Toko Harapan Baru requires a system that can be a solution to the problem that is being encountered. The Analytical Hierarchy Process (AHP) method is a functional hierarchy to help decision-makers better in making decisions on many objective issues.